2021
DOI: 10.1002/adma.202106232
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Volume Expansion of MoS3 Anode by Structure Engineering to Achieve High Performance Beyond Lithium‐Based Rechargeable Batteries

Abstract: Beyond‐lithium‐ion storage devices are promising alternatives to lithium‐ion storage devices for low‐cost and large‐scale applications. Nowadays, the most of high‐capacity electrodes are crystal materials. However, these crystal materials with intrinsic anisotropy feature generally suffer from lattice strain and structure pulverization during the electrochemical process. Herein, a 2D heterostructure of amorphous molybdenum sulfide (MoS3) on reduced graphene surface (denoted as MoS3‐on‐rGO), which exhibits low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(62 citation statements)
references
References 82 publications
1
54
0
Order By: Relevance
“…Recently, sodium-ion batteries (SIBs) have captured widespread attention due to the rich sodium resources in nature, environmental friendliness, low cost, and electrochemical properties similar to lithium. [6,[9][10][11] In particular, the Contemporary Amperex Technology Co. Limited of China unit of the ligand as single active center continuously store cations and anions via three-electron reactions. Additionally, Xia et al reported a conductive Cu-MOF nanowire hybrid structure based on arrays arranged on a self-supporting polypyrrole film, which exhibits excellent electrochemical performance and mechanical flexibility as an all-solid-state flexible supercapacitor electrode in a wide temperature range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, sodium-ion batteries (SIBs) have captured widespread attention due to the rich sodium resources in nature, environmental friendliness, low cost, and electrochemical properties similar to lithium. [6,[9][10][11] In particular, the Contemporary Amperex Technology Co. Limited of China unit of the ligand as single active center continuously store cations and anions via three-electron reactions. Additionally, Xia et al reported a conductive Cu-MOF nanowire hybrid structure based on arrays arranged on a self-supporting polypyrrole film, which exhibits excellent electrochemical performance and mechanical flexibility as an all-solid-state flexible supercapacitor electrode in a wide temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, not only the cost of commercial lithium-ion batteries (LIBs) increases due to the shortage of lithium resources, but also the performance of existing commercial LIBs has approached its limit. [5][6][7][8] Consequently, it is imminent to find alternative rechargeable batteries based on naturally abundant resources. Recently, sodium-ion batteries (SIBs) have captured widespread attention due to the rich sodium resources in nature, environmental friendliness, low cost, and electrochemical properties similar to lithium.…”
Section: Introductionmentioning
confidence: 99%
“…The contact angle tests (Figure 4g,h) showed that the amorphous MoS 3 -on-rGO electrode was endowed with a superior wetting property to the carbonate electrolyte owning to higher surface free energy of amorphous MoS 3 and unique 3D interconnected porous structure, contributing to an optimized ion diffusion kinetics during the electrochemical process. When applied as the anode for KIBs, it exhibits high specific capacity (541 mAh g −1 at a current density of 0.2 A g −1 ) and excellent long-term cycling stability, which is significantly superior to the corresponding crystal sample (Figure 4i,j) [53]. Ji et al took full advantage of element interaction to obtain phosphorus-doped amorphous carbon nanosheet (P-CNS) through thermal treatment, which achieved high performance as anode material for SIB.…”
Section: Rechargeable Batterymentioning
confidence: 98%
“…As depicted in Fig. 1 a, the seed crystals nucleated on the surface of carbon matrix usually undergo anisotropic growth, due to the large surface energy differences between diverse crystal planes [ 28 30 ]. Consequently, crystal nuclei of 2D materials favor to grow along the (100) and (010) planes with higher surface energy [ 31 , 32 ], forming nanostructures of 2D nanosheets standing on carbon matrix, i.e., heterostructures with line-to-face contact.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, by interfacial confining the anisotropic growth of the crystal nuclei via making the nuclei amorphous, as depicted in Fig. 1 b, the nuclei anchored on the matrix have the tendency of growing along the (001) plane with low surface energy, owing to isotropic growth behavior of the nucleates [ 28 , 33 ]. Such inhibition of the anisotropic growth would thus allow for transfer of the line-to-face growth of 2D nanosheets, to the face-to-face covering of 2D nanosheets on graphene.…”
Section: Introductionmentioning
confidence: 99%